The determinants and development of crowdfunding in the Central and Eastern Europe countries - Bednarz, Joanna; Markiewicz, Magdalena; Płoska, Agnieszka (Ekonomia i Prawo. Economics and Law, 2017)
Motivation: Crowdfunding (CF) is a method of raising money for projects and enterprises by online platforms. Since 2003 it is expanding and becoming a natural method of pre-financing for start-ups before reaching out to investors. The estimations gave the picture of fundraising worldwide at the level of 35 bln USD via CF platforms in 2015. Nevertheless, this method does not progress equally worldwide and it is essential to find what results in the difference in CF development among the countries. Aim: The aim of the article is to examine the relation between: (1) the welfare of countries, (2) structure of population and (3) availability of crowdfunding. The paper examines the countries of Central and Eastern Europe (CEE) for the period 2005–2015. Results: There is no direct correlation between GDP per capita of a country with it online per capita investments. The richness of a country does not influence people willingness to invest through online methods. In the countries of average level of welfare, alternative financing sources are used more widely. Moreover, there is a significant impact of the age structure of the population on crowdfunding development. Estonia has the youngest structure of population. Although there are not many inhabitants and the GDP per capita is average, the country has the most willing online crowd investors.